Simulation-Based Study Of Capacitance Values Affected By Various Dielectric Materials And Distances For Low Power Wireless Power Transfer System - Abdul Rahman, Farah Khalidah; Md Saat, Mohd Shakir; Yusop, Yusmarnita; Husin, Siti Huzaimah (Penerbit Universiti, UTeM, 2017)
Capacitive Power Transfer (CPT) system is nowadays getting better attention by some of the researchers who are focusing on wireless power transfer field. This is because of the simplicity, small size, and better reaction towards EMI characteristics of the method. Furthermore, the efficiency of the CPT system is greatly influenced by the coupling capacitances which are varied by distances and permittivity values. Thus, this paper attempts to converge into the effect of several dielectric materials towards capacitance values and also the effect of the capacitive plates’ distances towards the output power. By using Class E circuit configuration and MATLAB Simulink as the simulation software, the results are then explained graphically. From those simulations, the work achieved 90.7% as highest efficiency as compared to the theoretical values.